2016
DOI: 10.3389/fgene.2016.00208
|View full text |Cite
|
Sign up to set email alerts
|

The Worldwide Spread of the Tiger Mosquito as Revealed by Mitogenome Haplogroup Diversity

Abstract: In the last 40 years, the Asian tiger mosquito Aedes albopictus, indigenous to East Asia, has colonized every continent except Antarctica. Its spread is a major public health concern, given that this species is a competent vector for numerous arboviruses, including those causing dengue, chikungunya, West Nile, and the recently emerged Zika fever. To acquire more information on the ancestral source(s) of adventive populations and the overall diffusion process from its native range, we analyzed the mitogenome va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
100
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(119 citation statements)
references
References 54 publications
14
100
2
1
Order By: Relevance
“…Within the Torres Strait Islands it appears the population is of tropical, Indonesian origin and egg survival was lower in less humid conditions [77], supporting this conclusion. However, it is worth noting that there are multiple other COI haplotypes that do not conform to any obvious geographic patterns (S6 Fig), suggesting that there have been multiple introduction events into some locations from mainland Asia or potentially unsampled locations—a similar pattern which was also highlighted by other studies [9, 74]. The possibility of insertion of mtDNA in the nuclear genome [78, 79] was considered in this study and our COI sequences were assessed by examining chromatograms (no double peaks in chromatograms) and by checking for stop codons.…”
Section: Discussionsupporting
confidence: 72%
“…Within the Torres Strait Islands it appears the population is of tropical, Indonesian origin and egg survival was lower in less humid conditions [77], supporting this conclusion. However, it is worth noting that there are multiple other COI haplotypes that do not conform to any obvious geographic patterns (S6 Fig), suggesting that there have been multiple introduction events into some locations from mainland Asia or potentially unsampled locations—a similar pattern which was also highlighted by other studies [9, 74]. The possibility of insertion of mtDNA in the nuclear genome [78, 79] was considered in this study and our COI sequences were assessed by examining chromatograms (no double peaks in chromatograms) and by checking for stop codons.…”
Section: Discussionsupporting
confidence: 72%
“…Recent studies on genetic variation among A. albopictus native populations revealed geographic pattern of differentiation across large Southeast Asian Islands (Indonesia, Philippines), the Malaysian Peninsula (Malaysia, Thailand, Singapore), the western (Myanmar), and the eastern (Vietnam) Indochinese Peninsula, China, and Japan (Supporting Information Fig. S8; Battaglia et al 2016;Kotsakiozi et al 2017;Maynard et al 2017; Sherpa et al 2019). Here, we show that populations genetically differentiated at neutral loci (Fig.…”
Section: Native Populationssupporting
confidence: 63%
“…Evidence that most temperate invasive populations originated from near‐temperate regions within the native range (Battaglia et al. ; Kotsakiozi et al. ; Manni et al.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…After two introduction events in 1979 in Albania (Adhami & Murati, ) and 1990 in Italy (Sabatini, Raineri, Trovato, & Coluzzi, ), the species has progressively colonized all Southern European countries, and its geographical spread over time suggests an acceleration of the expansion process (European Centre for Disease Prevention and Control [ECDC], ). Broad‐scale phylogeographical studies have suggested independent introduction events in Europe and no apparent reduction in genetic diversity as compared to the native range (Battaglia et al, ; Goubert, Minard, Vieira, & Boulesteix, ; Kotsakiozi et al, ; Manni et al, ). These previous studies were based on sparse worldwide populations and did not focus on the demographic history in the invaded range.…”
Section: Introductionmentioning
confidence: 99%